Bibliographic organisation of continuing resources in relation to the IFLA models: Research within the Croatian corpus of continuing resources - Petrić, Tatijana (JLIS.it, 2016)
Comprehensive research on continuing resources has not been conducted in Croatia, therefore this paper will indicate the current bibliographic organisation of continuing resources in comparison to the parameters set by the IFLA models, and the potential flaws of the IFLA models in the bibliographic organisation of continuing resources, in comparison to the valid national code which is used in Croatian cataloguing practice. Research on the corpus of Croatian continuing resources was performed in the period from 2000 and 2011. By using the listed population through the method of deliberate stratified sampling, the titles which had been observed were selected. Through the method of observation of bibliographic records of the selected sample in the NUL catalogue, the frequency of occurrence of parameters from the IFLA models that should identify continuing resources will be recorded and should also show the characteristics of continuing resources. In determining the parameters of observation, the FRBR model is viewed in terms of bibliographic data, FRAD is viewed in terms of other groups or entities or controlled access points for work, person and the corporate body and FRSAD in terms of the third group of entities as the subject or the subject access to continuing resources. Research results indicate that the current model of bibliographic organisation presents a high frequency of attributes that are listed in the IFLA models for all types of resources, although that was not envisaged by the PPIAK, and it is clear that the practice has moved away from the national code which does not offer solutions for all types of resources and ever more so demanding users. The current model of bibliographic organisation of the corpus of Croatian continuing resources in regards to the new IFLA model requires certain changes in order for the user to more easily access and identify continuing resources. The research results also indicate the need to update the entity expression with the attribute mode of expression, and entity manifestation with the attributes mode of issuance, as well as further consideration in terms of the bibliographic organisation of continuing resources.